Spatiotemporal analysis of Polish municipal budget expenditure on selected categories of cultural institutions in the years 2003 to 2016 - Suchecki, Adam Mateusz (Journal of Public Governance, 2019)
Objectives: The main aim of the article is to analyse changes in spending on culture with regard to four selected groups: libraries, community cultural centres, heritage and monument protection, and others in the years 2003 to 2016. This article also looks at the sum of municipal budgets in individual provinces. Research Design and Methods: For the selected years, location quotients (LQ) were used to show the spatial diversity of cultural expenditure in the municipalities of particular voivodships. To illustrate the diversity of municipal expenditure on culture in particular years of the analysis was made using a dynamic modification of Knudsen’s regression model of share transfers proposed by Berzeg (the SSANOVA model). Findings: The increase in the share of cultural expenditure followed by a decline thereof may indicate that in 2011-2014 the municipalities in Poland made significant expenditure on culture, which could have been aimed at improving both hard and soft cultural infrastructure. Analysis using the Knudsen model revealed a disturbing tendency to decrease the share of municipal expenditure devoted to culture in total expenditure. Implications/Recommendations: The fact that the majority of municipalities in Poland in the analysed period devoted a higher share of expenditure to cultural purposes than average spending of this type for Poland may indicate a change in the approach of local authorities to the culture as a potential factor for the development of a municipality, rather than unnecessary budget expenditure. The downward trend in the share of cultural expenditure of municipalities in their total expenditure may, though not necessarily does, indicate a change in the direction of cultural policy of local governments in Poland. Contribution/Value Added: This approach opens new possibilities for analysing cultural expenditure from local budgets, as well as local cultural policies and the effectiveness of public finances.